Sistem Informasi Pengukuran Kinerja Pada Perkebunan Kelapa Sawit Dengan Menggunakan Metode Balanced Scorecard - Rosmiati, Rosmiati; Mustafid, Mustafid; Widiyanto, Ibnu (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
Palm oil plantations is one of the sub-sectors of agriculture crops in Indonesia, which is the main source of food and economic growth. The Balanced Scorecard (BSC) into a model of performance measurement system that can provide a solution within the framework of an integrated performance measurement using financial and non financial aspects. This study aims to develop information systems to measure the performance of oil palm plantations using the Balanced Scorecard method. Measurement of performance using four perspectives, that is: financial, customer, internal business processes and learning and growth. Nine indicators were used, that is: value of employee satisfaction, employee loyalty value, Return on Assets (ROA), solvency, crop maintenance, harvesting TBS, increasing the foreman and administrative competence in the garden, orchard manager guidance to employees and provide a special budget for training. This study resulted in an information system that can determine the weights of indicators and performance assessment scores will then be known to the achievement of performance measurement in oil palm plantations. This study was carried out on the Bina Karya plantation, obtained performance tends to be stable from 2009 to 2013. In 2011 the highest performance values ​​obtained at 68.34% and the lowest was in 2009 at 60.84%. Keywords: Performance Measurement; Balanced scorecard; Key Performance Indicator; Information System; Palm oil